1994
DOI: 10.1007/bf02052598
|View full text |Cite
|
Sign up to set email alerts
|

Life Table analysis of stomal complications following colostomy

Abstract: The evidence in this study that spans a 22-year period questions much surgical technical dogma and raises the possibility that parastomal hernias may, like inguinal hernias, represent a failure in the transversalis fascia that might technically be avoidable.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

9
266
5
34

Year Published

2000
2000
2018
2018

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 401 publications
(314 citation statements)
references
References 11 publications
9
266
5
34
Order By: Relevance
“…5 Persistently high morbidity and mortality rates associated with stoma creation and reversal are behind attempts to reduce their formation. Long-term complication rates of 58% in colostomies 6 and up to 76% in ileostomies 7 have been reported. It is also recognised that around 15% of temporary stomas created at the time of anterior resection become permanent.…”
mentioning
confidence: 99%
“…5 Persistently high morbidity and mortality rates associated with stoma creation and reversal are behind attempts to reduce their formation. Long-term complication rates of 58% in colostomies 6 and up to 76% in ileostomies 7 have been reported. It is also recognised that around 15% of temporary stomas created at the time of anterior resection become permanent.…”
mentioning
confidence: 99%
“…Londo-Schimmer et al [5] reported that the complication of paracolostomy hernia occurred in 43 out of 203 patients (21.1 %) after colostoma installation. In our institution, however, the paracolostomy hernia complication occurred in 6 out of 427 patients (1.4%) who had colostoma (Table 1).…”
Section: Discussionmentioning
confidence: 99%
“…Because of little postoperative invasion and prevention of recurrent adhesive ileus, laparoscopic operation is increasingly conducted to treat adhasive ileus [1][2][3]. Paracolostomy hernia and ileus have been reported in 21% and 5.4%, respectively of all late postoperative complications of colostomy [4,5]. The patient of this report suffered from a complication of paracolostomy hernia after abdominoperineal proctectomy and, as the result, adhesive ileus.…”
Section: Introductionmentioning
confidence: 99%
“…The correlation between the position of the stoma within the abdominal wall was studied by Sjodahl et al who demonstrated an advantage for enterostomy constructed through the rectus abdominis muscle [18], though in similar studies this association was not statistically significant [14,19,20]. One study has shown better results for extra-peritoneal positioning of the stoma, but there are no prospective randomized clinical trials comparing these two methods [13,19]. Other technical issues showing equivalent results are anchoring of the distal bowel segment to the abdominal wall [19,20], the site of hernia in relation to the main incision [21] and laparoscopic versus open approach [9].…”
Section: Risk Factor For the Development Of Phmentioning
confidence: 99%
“…When using an accurate measurement to create the trephine, the rate of PH dropped [17]. The correlation between the position of the stoma within the abdominal wall was studied by Sjodahl et al who demonstrated an advantage for enterostomy constructed through the rectus abdominis muscle [18], though in similar studies this association was not statistically significant [14,19,20]. One study has shown better results for extra-peritoneal positioning of the stoma, but there are no prospective randomized clinical trials comparing these two methods [13,19].…”
Section: Risk Factor For the Development Of Phmentioning
confidence: 99%